Climate Change Adaptation Strategies among Agricultural Cooperative Farmers in Southern Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined climate change adaptation strategies among agricultural cooperative farmers in Southern Nigeria. The specific objectives were to assess farmers’ perceptions of climate change and its effects on agricultural production, identify adaptation strategies adopted by cooperative farmers, determine the socioeconomic and institutional factors influencing adaptation decisions, and evaluate the effectiveness of agricultural cooperatives in enhancing adaptive capacity. The study adopted a survey research design and utilized a structured questionnaire to collect data from members of agricultural cooperative societies in selected states in Southern Nigeria. Data were analyzed using descriptive statistics while multiple regression analysis was employed to examine factors influencing adaptation strategy adoption. The findings revealed that cooperative farmers perceived climate change as a major threat to agricultural productivity through irregular rainfall, flooding, rising temperatures, pest infestations, and declining crop yields. Farmers adopted various adaptation measures, including crop diversification, adjustment of planting dates, use of improved crop varieties, irrigation farming, and soil conservation practices. The regression results showed that educational level, access to extension services, access to credit facilities, cooperative membership strength, and government support significantly influenced adaptation decisions. Among these factors, cooperative membership strength had the greatest influence on adaptation strategy adoption. The study concluded that agricultural cooperatives play a vital role in strengthening climate resilience and promoting sustainable agricultural development in Southern Nigeria. It recommended among others that government, agricultural agencies, and cooperatives should work to enhance climate change awareness and educational programs for farmers.
Keywords: Climate Change; Adaptation Strategies; Agricultural Cooperatives; Adaptive Capacity; Climate Resilience